2008
DOI: 10.1016/j.bmc.2007.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Novel analogs of d-e-MAPP and B13. Part 2: Signature effects on bioactive sphingolipids

Abstract: Novel isosteric analogs of the ceramidase inhibitors (1S,2R)-N-myristoylamino-phenylpropanol-1 (d-e-MAPP) and (1R,2R)-N-myristoylamino-4'-nitro-phenylpropandiol-1,3 (B13) with modified targeting and physicochemical properties were developed and evaluated for their effects on endogenous bioactive sphingolipids: ceramide, sphingosine, and sphingosine 1-phosphate (Cer, Sph, and S1P) in MCF7 cells as determined by high-performance liquid chromatography-mass spectrometry (HPLC-MS/MS). Time- and dose-response studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
2

Relationship

4
6

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 65 publications
(47 reference statements)
3
66
0
Order By: Relevance
“…The latter results, although unexpected for AC inhibitors, are not unprecedented. Bielawska et al ( 55 ) reported that the sphingolipid profi les of MCF-7 cells treated with different ceramidase inhibitors derived from B13 and D-e-MAPP followed different patterns depending on the chemical function substituted for the original amide. In the case of an N -alkyl analog of D-e-MAPP, namely, compound LCL284, ceramides accumulated, but long chain bases did not change signifi cantly.…”
Section: Discussionmentioning
confidence: 99%
“…The latter results, although unexpected for AC inhibitors, are not unprecedented. Bielawska et al ( 55 ) reported that the sphingolipid profi les of MCF-7 cells treated with different ceramidase inhibitors derived from B13 and D-e-MAPP followed different patterns depending on the chemical function substituted for the original amide. In the case of an N -alkyl analog of D-e-MAPP, namely, compound LCL284, ceramides accumulated, but long chain bases did not change signifi cantly.…”
Section: Discussionmentioning
confidence: 99%
“…P-gp is an anti-apoptotic membrane glycoprotein encoded by the MDR-1 gene, which could reduce the accumulation of chemotherapeutic drug in cells. P-gp could transport lots of hydrophobic lipophilic drugs such as colchicine, doxorubicin, vincristine out of cells using the energy released by ATP hydrolysis actively, decreased the intracellular drug concentration, redistributed the drugs, this all could lead to drug resistance (Veldman, 2004;Szulc, 2006;Bielawska, 2008). In a recent study, overexpression of SphK1 in RBE-4 cerebral endothelial cells was shown to enhance the expression of P-gp at the mRNA and protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that application of ceramide analogs or their mimetics induces apoptosis and/or growth arrest in various types of cancer cells (Bielawska et al 2008;Szulc et al 2006). It was clearly shown that there was significant inhibition of tumor growth and progression in response to ceramidoids, a recently synthesized ceramides, in head and neck squamous cancer cells and some other cancer models, in vivo (Bielawska et al 2008;Senkal et al 2006). Different structural analogs of ceramides have also been shown to induce apoptosis in breast cancer cells (Struckhoff et al 2004) and drug-resistant MCF-7/Adr cells (Crawford et al 2003).…”
Section: Discussionmentioning
confidence: 99%